2017
DOI: 10.18632/oncotarget.21406
|View full text |Cite
|
Sign up to set email alerts
|

The hOCT1 and ABCB1 polymorphisms do not influence the pharmacodynamics of nilotinib in chronic myeloid leukemia

Abstract: First-line nilotinib in chronic myeloid leukemia is more effective than imatinib to achieve early and deep molecular responses, despite poor tolerability or failure observed in one-third of patients. The toxicity and efficacy of tyrosine kinase inhibitors might depend on the activity of transmembrane transporters. However, the impact of transporters genes polymorphisms in nilotinib setting is still debated. We investigated the possible correlation between single nucleotide polymorphisms of hOCT1 (rs683369 [c.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…Because the role of CD34+/CD38–/CD26+ leukemic cells and pharmacogenetic/pharmacogenomic aspects have been already discussed in some of our previous works (720), in this study we focused on the gene expression profiling, in order to evaluate if de-regulation of some candidate genes at early time-points of therapy could impact on the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the role of CD34+/CD38–/CD26+ leukemic cells and pharmacogenetic/pharmacogenomic aspects have been already discussed in some of our previous works (720), in this study we focused on the gene expression profiling, in order to evaluate if de-regulation of some candidate genes at early time-points of therapy could impact on the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of several transmembrane drug transporters. They can be predictive of response or intolerance in CML patients: indeed, it has been demonstrated that single nucleotide polymorphisms (SNP) of hOCT1, ABCB1, and ABCG2 conditioned the imatinib pharmacokinetics and disposition whereas they did not impact on Nilotinib efficacy or toxicity (1620). This could be relevant in the decision of which kind of TKI has to be prescribed in the first line.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, TKIs function by binding to ATP-binding catalytic sites of the TK domains on RTKs or on non-RTKs, thereby, preventing TK phosphorylation and inhibiting down-stream intracellular signaling and transcription of genes such as pro-inflammatory cytokines. TKIs can also bind and occupy ATP- or substrate-binding sites on transmembrane transporters such as the hOTC1 influx protein and the ABC efflux pumps ( 64 66 ), thereby, affecting drug and cellular responses (right hand panel). RTK, receptor tyrosine kinase; TK, tyrosine kinase; hOCT1, human organic cation transport member 1; ABC, ATP-binding cassette; ABCB1, ABC sub-family B member 1 (P-glycoprotein 1); ATP, adenosine triphosphate; ADP, adenosine diphosphate; p, phosphate; NDB1, nucleotide binding domain 1; NDB2, nucleotide binding domain 2; TMD1, transmembrane domain 1; TMD2, transmembrane domain 2; TKI, tyrosine kinase inhibitor.…”
Section: Emerging Therapies For Chronic Graft-versus-host Diseasementioning
confidence: 99%
“…TKIs can also bind and occupy ATP- or substrate-binding sites on transmembrane transporters, such as the ATP-binding cassette (ABC) efflux pumps and the human organic cation transport member 1 (hOTC1) influx protein ( 64 66 ) thereby affecting drug and cellular responses ( Figure 2 , right hand panel). In CML, TKIs such as imatinib and dasatinib, have been shown to not only target and inhibit BCR-ABL1, but also c-KIT, PDGF receptor (PDGFR), and Src family kinases, which results in the abrogation of the transcription of pro-inflammatory cytokines such as IL-1, IL-6, and TNF-α, and prevents the proliferation of myeloid cells ( 70 ).…”
Section: Emerging Therapies For Chronic Graft-versus-host Diseasementioning
confidence: 99%
“…CML patients carrying the OCT1 c.480G allelic variant have lower clearance of imatinib than patients homozygous for the c.480C allelic variant [ 154 ]. However, clinical data indicates that CML patients with OCT1 polymorphisms that were negatively related with imatinib efficacy had no impact on nilotinib efficacy or toxicity [ 155 ].…”
Section: Slc22 Genetic Heterogeneity In Cancer Pharmacologymentioning
confidence: 99%